Comparison of Outcomes Associated with Tibial Plateau Levelling Osteotomy and a Modified Technique for Tibial Tuberosity Advancement for the Treatment of Cranial Cruciate Ligament Disease in Dogs: A Randomized Clinical Study - Livet, Véronique; Baldinger, Arnaud; Viguier, Éric; Taroni, Mathieu; Harel, Mathieu; Carozzo, Claude; Cachon, Thibaut (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives This study aimed to compare outcomes between the tibial plateau levelling osteotomy (TPLO) procedure and a modified tibial tuberosity advancement (TTA Rapid) in dogs with cranial cruciate ligament rupture.Materials and Methods Twenty-six dogs were prospectively randomized into two groups: a TPLO group (n = 13) and a TTA Rapid group (n = 13). A lameness score evaluation, gait analysis and radiographical examination were performed before surgery, the 3 days after surgery, and then at 1, 3 and 6 months postoperatively. Finally, owners were asked to subjectively rate their level of satisfaction.Results The duration of surgery was significantly shorter for the TTA Rapid procedure (p < 0.0001). There was no significant difference in the occurrence of complications between groups. Lameness scores were significantly higher during the first 3 days after surgery for the TPLO group (p = 0.01 at day 1, p = 0.01 at day 2 and p = 0.003 at day 3). One month after surgery, the symmetry index between healthy and affected limbs for the relative stance time during the gait cycle (symmetry index/%) was significantly higher for the TTA Rapid group (p < 0.01). No gait parameters were significantly different between the two groups 6 months after surgery. All of the owners of dogs in the TPLO group were completely satisfied, whereas only 11/13 owners of dogs in the TTA rapid group were completely satisfied.Clinical Significance Tibial plateau levelling osteotomy and TTA Rapid were associated with high long-term success rates in dogs. The immediate postoperative recovery seemed faster with TTA Rapid, but thereafter there was no difference.
Keywords: dogs; cruciate ligament disease; tibial plateau levelling osteotomy; tibial tuberosity advancement; lameness score